Pengaruh Kepemimpinan Transformasional dan Lingkungan Kerja Non Fisik Terhadap Turnover Intention Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada PT Saba Pratama - Sandra, Mela; Khurosani, Aan (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2019)
This study aims to examine and analyze the effect of transformational leadership and non-physical work environment on turnover intention through job satisfaction as an intervening variable at PT Saba Pratama. The method used in this research is descriptive analysis method with a quantitative approach, namely research with quantitative data which is then processed and analyzed for conclusions. The number of samples in this study was 115 employees. This research uses saturated sample technique. Data collection methods in this study were carried out in several ways including questionnaire method, observation and interview methods. Data analysis techniques are in accordance with the research pattern and the variables to be studied. In this study used structural Equation Modeling (SEM) analysis which is a multivariate analysis. SEM is a statistical model that seeks to explain the relationship between many variables. To do SEM analysis, the tools or software used in this study are used SmartPLS. The results show that transformational leadership has a negative and significant influence on turnover intention. Non-physical work environment has a negative and significant influence on turnover intention. Transformational leadership has a positive and significant influence on job satisfaction. Non-physical work environment has a positive and significant influence on job satisfaction. Job satisfaction has a negative and significant influence on turnover intention